PROFITABILITAS SEBAGAI MEDIATOR DALAM PENGARUH DIVERSITY DAN INCLUSION TERHADAP NILAI PERUSAHAAN DI INDONESIA - Attamimi, Fauzan; Sundari, Siti (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2025)
This study aims to analyze the impact of diversity, inclusion, and profitability on firm value and the role of profitability as a mediator in companies in the basic materials sector. This study applies a quantitative approach. The data used are secondary data obtained from the company's annual report and sustainability report. The data were analyzed using SPSS software through a series of analytical methods such as descriptive statistical analysis, classical assumption tests, path analysis, and hypothesis testing. The findings of this study indicate that diversity and inclusion have an influence on firm value and profitability. Furthermore, profitability is proven to significantly impact firm value, but cannot act as a mediator in the relationship between diversity and inclusion on firm value. These findings indicate that diversity and inclusion practices not only have a direct impact on firm value but also strengthen the company's profitability performance. This study enriches the literature on the role of diversity and inclusion in the context of firm value and provides the latest empirical evidence in the material-based industrial sector. These results emphasize the importance of managing diversity and inclusion as a long-term strategy to increase organizational trust and stability.